2018
DOI: 10.1080/09637486.2018.1486393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mate tea (Ilex paraguariensis) on the expression of the leukocyte NADPH oxidase subunit p47phox and on circulating inflammatory cytokines in healthy men: a pilot study

Abstract: Increased superoxide production by phagocytic NADPH oxidase has been associated with inflammatory conditions. Growing evidences suggest that dietary polyphenols may modulate the expression of NADPH oxidase subunits. Herein, we examined whether soluble mate tea (SMT) consumption - a polyphenol-rich beverage - affects the expression of the leukocyte NADPH oxidase protein p47 and/or circulating biomarkers of inflammation and antioxidant biomarkers in humans. In a two-phase study, nine men were requested to drink … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The importance of medicinal plants as a complementary and alternative medicine have been increasing worldwide, all over the years and secondary metabolites of yerba mate and curcumin have become an important strategy against ROS and reducing inflammatory disorders (Alizadeh et al, 2018; Panza, Brunetta, de Oliveira, Nunes, & da Silva, 2019). Moreover, several studies have demonstrated the efficacy of antioxidant supplementation in people with disabilities (Navarrete‐Opazo, Cuitiño, & Salas, 2017; Parisotto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of medicinal plants as a complementary and alternative medicine have been increasing worldwide, all over the years and secondary metabolites of yerba mate and curcumin have become an important strategy against ROS and reducing inflammatory disorders (Alizadeh et al, 2018; Panza, Brunetta, de Oliveira, Nunes, & da Silva, 2019). Moreover, several studies have demonstrated the efficacy of antioxidant supplementation in people with disabilities (Navarrete‐Opazo, Cuitiño, & Salas, 2017; Parisotto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Blood glutathione (GSH) was 16.5% higher in SMT than in the control treatment. SMT ingestion favorably affected inflammatory cytokine and antioxidants levels in peripheral blood, which may help decrease oxidative stress and low-grade inflammation Controlled Clinical Trial (Panza et al 2019 ) I. paraguariensis 3 g of a preparation containing soluble yerba mate plus maltodextrin and artificial peach flavor, corresponding to 107 mg/g total phenols, or mate-placebo for 15 days each, alternating by a washout period of 15 days In 92 individuals on antiretroviral therapy for at least six months and at viral suppression, mean values of HDL-c (mg/dL) at baseline and after receiving yerba mate and placebo mate were 50.6 ± 15, 50.3 ± 14.6, respectively. Fibrinogen levels were within the normal range in 71.7% of the subjects.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo studies show that infusion could inhibit oxidation of LDL (low density lipoprotein), also contributing to treatments of obesity, diabetes, and arteriosclerosis (Godoy et al, 2013;Habtemariam, 2019;Luís et al, 2019). Recent research has shown numerous therapeutic qualities of yerba mate, including hepatoprotective, neuroprotective, resistance against oxidative stress, antiobesity, cardioprotection, and antioxidant effects ( Figure 5) (Baeza et al, 2017;Cahuê et al, 2019;Cittadini et al, 2019b;Panza et al, 2018;Valenca et al, 2019).…”
Section: Chemical Aspects Bioactive Compounds and Their Functionalitiesmentioning
confidence: 99%